"Beginning With the End in Mind": Imagining Personal Retirement Speeches to Promote Professionalism. (June 2015) - Yu, Eunice; Wright, Scott M.
Abstract : Problem: The goal of teaching professionalism in medicine is to transform a theoretical concept into an internalized and actualized identity. Many trainees struggle with professionalism in the abstract, particularly when instruction methods are didactic and disconnected from personal experience. Approach: The authors aim to demonstrate the feasibility of having interns frame a personal definition of professionalism based on a reflective technique called "beginning with the end in mind." Interns composed remarks that might be used to introduce them at their own retirement ceremony following a career in medicine. This "career eulogies" exercise was introduced to groups of six interns during the first third of the internship year as part of a two-week curriculum focused on professional development. Two investigators independently coded the written introductions, identifying emergent themes through content analysis. Outcomes: Of the 19 interns in an internal medicine residency program (2012–13), 17 participated in the exercise. Six themes emerged from the data: aligning behaviors with core values, achieving excellence in medicine, changing the world and giving back, valuing teamwork and relationships, realizing work–life balance, and appreciating a career in medicine. These themes correlate with accepted published definitions of professionalism. Next Steps: The personal reflections produced through this exercise allow physicians to begin to formulate their professional self-conception. Extensions of this work might include linking such forms of critical reflection to individualized learning plans and updating the speeches over time. Further research on "reflecting forward" may determine its impact as a complement to traditional narrative reflection.